Negotiating Journalistic Professional Ethos in Nordic Business Journalism - Suhonen, Johanna (2022)
News work conducted more like business creates clashes between the journalistic and managerial professional ethos of editors. While journalists’ professional ethos includes values of self-regulation, autonomy, and public service, managerialism promotes business ideals, measurable outcomes, and organizational efficiency—values that business journalism is claimed to support. This article aims to show how editors negotiate their work-related ethos at the junction of two professional discourses. The article is based on 20 semi-structured interviews of editors in four Nordic business newsrooms. The results reveal a new hybrid professional ethos that combines managerial practices with journalistic ideals. Furthermore, editors in business journalism tend to absorb managerial tendencies more easily due to close connection to financial and commercial communities. Strong journalistic principles prevail, but managerial ideals are considered a notable part of the new editorial work ethos.